How Do Residents Spend Their Shift Time? A Time and Motion Study With a Particular Focus on the Use of Computers - Mamykina, Lena (Acad Med, 2016)
PURPOSE: To understand how much time residents spend using computers as compared with other activities, and what residents use computers for. METHOD: This time and motion study was conducted in June and July 2010 at NewYork-Presbyterian/Columbia University Medical Center with seven residents (first-, second-, and third-year) on the general medicine service. An experienced observer shadowed residents during a single day shift, captured all their activities using an iPad application, and took field notes. The activities were captured using a validated taxonomy of clinical activities, expanded to describe computer-based activities with a greater level of detail. RESULTS: Residents spent 364.5 minutes (50.6%) of their shift time using computers, compared with 67.8 minutes (9.4%) interacting with patients. In addition, they spent 292.3 minutes (40.6%) talking with others in person, 186.0 minutes (25.8%) handling paper notes, 79.7 minutes (11.1%) in rounds, 80.0 minutes (11.1%) walking or waiting, and 54.0 minutes (7.5%) talking on the phone. Residents spent 685 minutes (59.6%) multitasking. Computer-based documentation activities amounted to 189.9 minutes (52.1%) of all computer-based activities time, with 128.7 minutes (35.3%) spent writing notes and 27.3 minutes (7.5%) reading notes composed by others. CONCLUSIONS: The study showed residents spent considerably more time interacting with computers (over 50% of their shift time), than in direct contact with patients (less than 10% of their shift time). Some of this may be due to an increasing reliance on computing systems for access to patient data, further exacerbated by inefficiencies in the design of the electronic health record.